When this is over : reflections on an unequal pandemic - Cortvriend, Amy; Easthope, Lucy Catherine; Edkins, Jenny; Purnell, Kandida; Black, Sue; Younge, Gary; Younge, Gary; Rosen, Michael; Hall, Fran (Policy Press, 2023)
The COVID-19 pandemic had a profound and persistent impact. A tragic loss of life, change to established patterns of life and social inequalities laid bare. It brought out the good in many and the worst in others and raised questions around what is truly important in our lives. In this book, academics, activists and artists come together to remember and to reflect on the pandemic. What lessons should we learn? And how can things be different when this is over? Sensitive to inequalities of gender, race and class, it highlights the experience of marginalised and minority groups and the unjust and uneven spread of violence, deprivation and death. It combines academic analysis with personal testimonies, poetry and images from contributors including Sue Black, Led By Donkeys, Lucy Easthope, Lara- Rose Iredale, Michael Rosen and Gary Younge. Taken together, this truly inclusive commemorative overview honours the experience of a global disaster lived up close and suggests the steps needed to ensure we do better next time.